9+9m=-9+6m+5m

Simple and best practice solution for 9+9m=-9+6m+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+9m=-9+6m+5m equation:


Simplifying
9 + 9m = -9 + 6m + 5m

Combine like terms: 6m + 5m = 11m
9 + 9m = -9 + 11m

Solving
9 + 9m = -9 + 11m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11m' to each side of the equation.
9 + 9m + -11m = -9 + 11m + -11m

Combine like terms: 9m + -11m = -2m
9 + -2m = -9 + 11m + -11m

Combine like terms: 11m + -11m = 0
9 + -2m = -9 + 0
9 + -2m = -9

Add '-9' to each side of the equation.
9 + -9 + -2m = -9 + -9

Combine like terms: 9 + -9 = 0
0 + -2m = -9 + -9
-2m = -9 + -9

Combine like terms: -9 + -9 = -18
-2m = -18

Divide each side by '-2'.
m = 9

Simplifying
m = 9

See similar equations:

| -16=30x+15x^2 | | 6x-15x=18 | | -2x-39=-6x+29 | | 6a+4a-3a= | | 63x^8=0 | | 4k+ar=r-7y | | -3(t-5)+5t=7t-4 | | X^2+6x-1=7x-9 | | -4.19+11.5c=10c-0.87+1.7c | | 6x+3x-6=10x+5 | | -8-5v=-9v | | -4y+8z=32 | | -5-8a=-45 | | X+6=5(2x-2) | | y(x^2+y^2)dx=x^3dy | | -2-10w=4-8w | | r=9.6 | | 14+12w=16+9w | | -11(4+k)=220 | | 15x(-2-x)-12=4 | | (3.14)x^2=28.26 | | 3q-2=7 | | -8m=4 | | 6r+10=124 | | -2b+6-4=18 | | -6u=10-5u | | 5.9s=3(-3.4s-15.91) | | 5x+6=16x+-3x+54 | | x-10=104 | | -3(8+n)=33 | | 6(x+1)-2=3x-12 | | 5x+6=16x-3x |

Equations solver categories